Checklist of leaf beetles (Coleoptera: Chrysomelidae) from the state of Morelos, Mexico - Niño-Maldonado, Santiago; Sánchez-Reyes, Uriel Jeshua; Clark, Shawn M.; Toledo-Hernández, Victor Hugo; Corona-López, Angélica María; Jones, Robert W. (Zootaxa, 2016)
We record 116 genera and 366 species of Chrysomelidae from the state of Morelos, Mexico. This represents an increase of 9.3% in the species richness of these beetles for the state. Also, Morelos is currently the third most diverse state in leaf beetles within Mexico, with 16.78% of total species recorded for the country. The most diverse genera were Calligrapha, Disonycha, Blepharida, Leptinotarsa, Cryptocephalus, Systena, Alagoasa, Diabrotica and Pachybrachis, each with more than eight species. Most of these genera contain large, showy beetles. When the chrysomelid fauna is more fully understood, some of the genera of tiny beetles will likely prove to be more diverse.